Carbene-catalyzed enantioselective addition of thioamides to bromoenals for access to thiazinone heterocycles - Liu, Changyi (2020)
A carbene-catalyzed reaction between α-bromoenals and thioamides was developed. Key steps include enantioselective 1,4-addition of thioamide sulfur atoms to α,β-unsaturated acyl azolium intermediate. Subsequent intramolecular annulation eventually affords thiazinone heterocycles with high optical purities. The introduction of Lewis acid additives such as Cu(OTf)2 to this NHC catalytic reaction could provide small but consistent improvements to reaction enantioselectivities.